La bodega - Figueroa, Ray; Pineda, Luis Carlos (Casa Comal, 2009)
"A young woman is brutally assaulted by gang members in the middle of Guatemala City. As usual, the authorities have no suspects or leads, leaving the girl to become one more victim in a society where thousands of women are assaulted every year. Jacobo, the victims brother, along with Antonio, his best friend, decide in their frustration to extract some of their kind of revenge. They kidnap a random gang member from the streets and drive him to an abandoned warehouse, where they torture and beat him. But the consequences of their acts will soon become evident and they will have to make a decision that will affect their lives forever"--Internet Movie Database.